ChemInform Abstract: External Oxidant‐Free Oxidative Cross‐Coupling: A Photoredox Cobalt‐Catalyzed Aromatic C—H Thiolation for Constructing C—S Bonds. Issue 3 (29th December 2015) - Zhang, Guoting; Liu, Chao; Yi, Hong; Meng, Qingyuan; Bian, Changliang; Chen, Hong; Jian, Jing‐Xin; Wu, Li‐Zhu; Lei, Aiwen
Abstract: A variety of benzothiazoles is obtained by an intramolecular oxidative photocyclization of corresponding N‐arylthioamides.